THE RELATION BETWEEN WORK-LIFE BALANCE AND EMPLOYEE WELL- BEING AMONG EMPLOYEES - Anggraini, Ramadani Fitria; Izzati, Umi Anugerah (Penerbit Lafadz Jaya, 2026)
This study examines the relationship between work–life balance and employee well-being among 93 employees working in a social service institution. This topic is important because employees in social-based organizations often face emotional demands and high workload intensity that can disrupt balance and reduce overall well-being. Based on Hudson's (2005) work–life balance model and Zheng's (2015) employee well-being framework, this study hypothesizes that higher work–life balance is associated with higher well-being. The study employs a quantitative correlational design with purposive sampling. Data were collected through a 42-item Likert-scale questionnaire and analyzed using SPSS, including assumption tests (normality) followed by Pearson or Spearman correlation depending on data distribution. The findings show a significant positive relationship between work–life balance and employee well-being, highlighting the importance of organizational policies that support balanced work demands to enhance the psychological, social, and workplace well-being of social service employees.